2003
DOI: 10.1177/030089160308900209
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Concomitant Radiotherapy and Chemotherapy in Ultrasound-Staged T3 and T4 Rectal Cancer

Abstract: Preoperative chemoradiotherapy seems to be an effective and well-tolerated treatment with a low complication rate. The high percentage of down-staging and sphincter sparing, also in distal rectal cancer, shows the efficacy of the treatment, which could significantly influence the incidence of relapses and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…After a median follow-up of four years, the four-year, disease-free and overall survival rates were 67.6 and 80.1 percent, respectively, which are similar to the rates found with preoperative radiochemotherapy and postoperative chemotherapy for Stage II and Stage III. 9,30-32 Whereas retrospective analyses have shown that achieving a pCR improves long-term outcomes,30,[32][33][34][35] all pCR patients in the present study were recurrence free and only one patient (1.3 percent) recurred in Grade 2, after resection, and the patient has survived.…”
mentioning
confidence: 60%
“…After a median follow-up of four years, the four-year, disease-free and overall survival rates were 67.6 and 80.1 percent, respectively, which are similar to the rates found with preoperative radiochemotherapy and postoperative chemotherapy for Stage II and Stage III. 9,30-32 Whereas retrospective analyses have shown that achieving a pCR improves long-term outcomes,30,[32][33][34][35] all pCR patients in the present study were recurrence free and only one patient (1.3 percent) recurred in Grade 2, after resection, and the patient has survived.…”
mentioning
confidence: 60%
“…Patients who underwent preoperative vs. postoperative radiation were more likely to be missing staging information or to have earlystage disease. We are not able to determine whether those differences were caused by a complete pathologic tumor response (which occurs in 10 percent to [17][18][19][20] ; by downstaging because of partial tumor response after radiation; by uncertainty on the part of the person doing the staging as to how to interpret AJCC rules after preoperative therapy; by inadequate nodal evaluation; or by other factors. However, given the increasing rate of preoperative radiation therapy use, researchers using the SEER database in the future must carefully consider its influence on stage distribution in SEER.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Encouraging results also have been achieved in terms of recurrence rate 7,8 and survival, 9,10 even if in most of the published series the median follow-up period is too short to consider the results conclusive. [11][12][13][14] This study was designed to evaluate the long-term results of our series of 83 cases of locally advanced resectable extraperitoneal rectal cancer submitted to neoadjuvant radiochemotherapy between 1990 and 1995, on the base of a complete follow-up for the living patients of, at least, nine years.…”
mentioning
confidence: 99%